UMPSA establishes collaboration with Islamic Azad University, Iran - Mohd Ferdaus, Musa (UMPSA, 2023)
RAN, 8 October 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to strengthen its name through visibility and reputation as a leading technological university by signing an MoU related to science and technology with the Islamic Azad University, the Islamic Republic of Iran, which is the world's largest comprehensive educational institution.